Characterization of a temperate forest in an altitudinal gradient in Oaxaca, Mexico - Velasco Luis, Mario Ubaldo; Velázquez Martínez, Alejandro; Hernández de la Rosa, Patricia; Fierros González, Aurelio Manuel; Vera Castillo, José Amando Gil (Instituto de Ecología, A.C., 2023)
Characterization of the vegetation helps to generate management and conservation guidelines, however, few studies in temperate forests integrate the understory vegetation. The objective of this study was to describe the structure, composition, and tree, shrub, and herbaceous floristic diversity of the pine-oak forest in an altitudinal gradient in the community of Miguel Hidalgo, San Antonio Huitepec, Oaxaca. Dasometric variables were taken at 45 sites distributed in three altitudinal intervals. Alpha and beta diversity were estimated, as well as the importance value index, and compared among intervals. 27 tree species, 25 shrubs and 73 herbaceous were identified. A medium diversity was determined for trees and herbs, and low for shrubs. The diversity of the three life forms did not present a defined distribution pattern; however, the upper altitudinal interval presented the highest average value of basal area, height, and individual coverage. Pinus oocarpa Schiede., Gaultheria erecta Vent. and Pteridium aquilinum var. feei (W. Schaffn. ex Fée) Maxon presented the highest value of the importance value index in the lower and intermediate altitudinal range, and Pinus pseudostrobus Lindl. and Salvia cinnabarina M. Martens & Galeotti in the upper altitudinal range. The upper altitudinal interval presented a better state of conservation influenced by less anthropogenic disturbance. Considering the understory in characterization studies improves the understanding of the dynamics of growth and development of forest vegetation.